A funcionalidade objetiva do testamento como expressão de liberdade no planejamento sucessório - Galluci, Fernanda Fernandes (2019)
The will is an instrument of great importance in inheritance law and succession planning and, consequently, a form of exercise of freedom by the proprietor of the patrimony in the destination of his assets after his death, which direction finds limitations in the Federal Constitution and the Brazilian Civil Code. In this paper, we will study the limitations to the exercise of the freedom to elaborate a will through the analysis of hereditary succession, the conditions for the legitimacy and ability to draw up the will, the order of hereditary vocation that must be respected and the particularities of each form of will be studied, including distinguishing between the succession reflexes of each of the property regimes of marriage. Will also be analyzed the modalities of will, the limits of wills - considering the existence of legitimate heirs, the possibility of establishing legacies of various species and recording inherited property with restrictive clauses -, and the characteristics and requirements of each form of testing to be valid and effective, achieving the purpose of fulfilling the will of the tester upon death. Inheritance, although constitutionally guaranteed to the necessary heirs, may be the object of renunciation by such heirs or of exclusion of these heirs by the testator, through the institutes of indignity and disinheritance, whose particularities are studied under the testamentary approach